SOCIAL COMMUNICATION IN THE FIQH TAFSÎR: A Study of Muslims and Non-Muslims in the Qur’anic Interpretation - Hamdan, Ali (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: This study is driven by a reality showing a social communication in a factual Fiqh interpretation between Muslim and non-Muslim in the Qur’an. Therefore, the question that needs to be answered is “how the fiqh interpretation can depict the social communication between Muslims and non-Muslims in the Qur’an?” This is a qualitative study, which is also a library study, and the whole data source is a written documentation. This study has depicted the social communication occurred between Muslims and non-Muslims through the Qur’an. The Qur’an mentioned that Islam and Muslim are parts of a belief, but it also mentions about non-Muslim in a samawi scope, which are Yahudi, Nasrani and Ahl al-Kitab. The social communication between Muslims and non-Muslims is also detected in the Qur’an comprising topics like knowing each other, conducting a convention of peace, and a more lenient relationship with the Christians because of the same origin and an equivalent dialog with the believers of Ahl al-Kitab in a topic that doubts the Oneness of Allah the Almighty.Keywords: social communication, fiqh tafsîr, Qur’anic exegesis, Muslim, Non-Muslim